DIGITALISASI BIROKRASI MELALUI IKD (IDENTITAS KEPENDUDUKAN DIGITAL) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DI KOTA PALANGKA RAYA - Shinta, Melia; Nadya Grestyana (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
Advances in information technology and telecommunications have brought Indonesia into the digital era. Digitalization has rapidly changed the paradigm of people's lives, including in terms of public services which are felt to be very different from those of several decades before. Public service innovation must have relative advantages compared to previous services, including the value of novelty that differentiates it. One of the agencies that provides public services is the Department of Population and Civil Registration (DISDUKCAPIL) in terms of digitizing the bureaucracy and then launching an application that contains population-related information in digital form. The aim of this research is to analyze the digitalization of bureaucracy carried out by DUKCAPIL through the IKD application. The type of research used uses a qualitative approach. Informants are determined using the snowball technique which is closely related to the research topic. The findings from the research are that the digitization of bureaucracy through Digital Population Identity (IKD) in the Palangka Raya City Population and Civil Registration Service has gone well, however, it is necessary to pay attention to the increase in staff who handle IKD as well as more thorough socialization to the community so that this IKD can achieve the targets set. has been set